Implementasi Nilai-Nilai Pendidikan Agama Islam Pada Program Adiwiyata Di SMA Negeri 4 Kota Bengkulu - Alvin Syaputra; Kasmantoni Kasmantoni; Ahmad Walid (GHAITSA : Islamic Education Journal, 2021)
This research is in SMA Negeri 4 Bengkulu City. The purpose of the study was to determine the implementation of Islamic religious education values in the implementation of the Adiwiyata program at SMA Negeri 4 Bengkulu City. The type of research used is descriptive qualitative research by taking the research place at SMA Negeri 4 Bengkulu City. Data collection is done by using the method of observation, interviews and documentation. The data analysis used is an interactive data model analysis, which consists of data reduction activities (data reduction), data presentation (data display), and conclusion drawing and testing (drawing and verifying conclusions). The results showed that the implementation of Islamic religious education values at the Adiwiyata National School of SMA Negeri 4 Bengkulu City was well realized through the guidance carried out by the school through religious habits, as well as activities containing Adiwiyata values that were scheduled and well structured. In which there are three kinds of coaching, namely the formation of aqidah, the formation of worship and the formation of morality.